2022
DOI: 10.3233/xst-211073
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of diabetic retinopathy using custom convolutional neural network

Abstract: Diabetic retinopathy is an eye deficiency that affects retina as a result of the patient having diabetes mellitus caused by high sugar levels, which may eventually lead to macular edema. The objective of this study is to design and compare several deep learning models that detect severity of diabetic retinopathy, determine risk of leading to macular edema, and segment different types of disease patterns using retina images. Indian Diabetic Retinopathy Image Dataset (IDRiD) dataset was used for disease grading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Next, the proposed DL-KS segmentation technique is combined with several CNN architectures including Alex-Net [29], Inception-v3 [30], ResNet-50 [29], VGG-16 [31] and VGG-19 [32]. Figure 16 ree other datasets, such as Kaggle [33], Messidor [34], and DDR [35], are also used as the testbed for analyzing the performance of the proposed DS-KL segmentation technique.…”
Section: Implementation and Discussionmentioning
confidence: 99%
“…Next, the proposed DL-KS segmentation technique is combined with several CNN architectures including Alex-Net [29], Inception-v3 [30], ResNet-50 [29], VGG-16 [31] and VGG-19 [32]. Figure 16 ree other datasets, such as Kaggle [33], Messidor [34], and DDR [35], are also used as the testbed for analyzing the performance of the proposed DS-KL segmentation technique.…”
Section: Implementation and Discussionmentioning
confidence: 99%
“…The experimental results showed that VGG16 with fine-tuning can achieve a higher accuracy of 71.65% than that of GoogLeNet. Albahli et al [144] adopted three pre-trained models, that is, ResNet50, VGG16, and VGG19, to identify both DR severity and the risk of ME. The best accuracy of 82.5% was achieved by ResNet50 performed on original images.…”
Section: B Multi-class Classification For Gradingmentioning
confidence: 99%
“…1,2 Advanced ML techniques based on deep neural networks have been reported for various detection and prediction tasks for people with Type 1 diabetes (T1D), ranging from development of a recurrent neural network (RNN) to predict adverse glycemic events 3 and detection of retinopathy. 4,5 This work focuses on the detection and classification of prior meal and physical activity events from long-term historical data of individuals with T1D. One of the objectives is to assess the need for data reconciliation and imputation because continuous glucose monitoring (CGM) data under free-living conditions may have many missing values, outliers, and incomplete diaries for meals and physical activities.…”
Section: Introductionmentioning
confidence: 99%